PENGEMBANGAN PARIWISATA KABUPATEN KEPULAUAN TALAUD PROVINSI SULAWESI UTARA - Koondoko, Yovanca Yully Feniaty; Darma Putra, I Nyoman; Paturusi, Syamsul Alam (Jurnal Master Pariwisata (JUMPA), 2017)
This article analisys tourism development strategy of Talaud regency, North Sulawesi Province. This regency has a great tourism potential but faces vaious problems. Its tourism potentials is evidenced from the diversity of the natural, culture, and man made tourism attractions. The great tourism potential has not been able to make Talaud widely known by tourists. As the outermost regions, the problems of accessibility are the main obstacles faced by the region of Talaud Islands. Other obstacles such as limited electricity and telecommunication access, and the lack of supporting facilities of tourism activities, have an impact, on the slow development of tourism potential in Talaud. Stages in the research were: described the potentials of tourism, then explained the obstacles that hinder the potential, and finally formulated strategies for the development of tourism potentials. SWOT matrix analysis is used to find the strategies to develop the tourism potential in Talaud. S-O strategy includes the development strategy of attraction. S-T strategy is the institutional strategy. W-O strategy includes the development strategy of public facilities and the supporting facilities at each tourist attraction. W-T strategy includes the making of programs intended for the community participation.